The steady-state transcriptome of the four major life-cycle stages of Trypanosoma cruzi - Orlando Ron; Atwood James; Weatherly D Brent; Minning Todd A; Tarleton Rick L (BMC Genomics, 2009)
Abstract Background Chronic chagasic cardiomyopathy is a debilitating and frequently fatal outcome of human infection with the protozoan parasite, Trypanosoma cruzi. Microarray analysis of gene expression during the T. cruzi life-cycle could be a valuable means of identifying drug and vaccine targets based on their appropriate expression patterns, but results from previous microarray studies in T. cruzi and related kinetoplastid parasites have suggested that the transcript abundances of most genes in these organisms do not vary significantly between life-cycle stages. Results In this study, we used whole genome, oligonucleotide microarrays to globally determine the extent to which T. cruzi regulates mRNA relative abundances over the course of its complete life-cycle. In contrast to previous microarray studies in kinetoplastids, we observed that relative transcript abundances for over 50% of the genes detected on the T. cruzi microarrays were significantly regulated during the T. cruzi life-cycle. The significant regulation of 25 of these genes was confirmed by quantitative reverse-transcriptase PCR (qRT-PCR). The T. cruzi transcriptome also mirrored published protein expression data for several functional groups. Among the differentially regulated genes were members of paralog clusters, nearly 10% of which showed divergent expression patterns between cluster members. Conclusion Taken together, these data support the conclusion that transcript abundance is an important level of gene expression regulation in T. cruzi. Thus, microarray analysis is a valuable screening tool for identifying stage-regulated T. cruzi genes and metabolic pathways.